Enriching the methanol generation via CO2 photoconversion over the cockscomb-like fibrous silica copper. (15th November 2022) - Bahari, M.B.; Mamat, C.R.; Jalil, A.A.; Shing, L.S.; Hassan, N.S.; Aziz, F.F.A.; Alhassan, M.; Nawawi, M.G.M.; Kidam, K.; Setiabudi, H.D.
Graphical abstract: Highlights: Cockscomb-like fibrous silica copper was fabricated via a microemulsion approach. Huge surface area and excellent CuO dispersion triggered the superior yield of CH3 OH (412.4 µmol gcat −1 h −1 ). Intense interaction resulted from an alternate arrangement of CuO-SiO2 in FSCu. Ideal bandgap and band edge positions of FSCu for CO2 photoconversion. The positive enhancement by rising the CO2 flowrate and sacrificing agent amount. Abstract: Carbon dioxide (CO2 ) photoconversion into methanol (CH3 OH) was recognized as a beneficial approach to overcoming future energy and environmental issues. Here, CO2 photoconversion into CH3 OH was intensively evaluated over fibrous silica-copper (FSCu) and copper-supported fibrous silica (CuO/KCC-1) generated through a microemulsion and incipient wetness impregnation approach, respectively. The physicochemical attributes of the generated photocatalysts were characterized via UV–vis spectroscopy, X-ray diffraction, N2 physisorption, Field-emission scanning electron microscopy, and Fourier-transform infrared spectroscopy analysis. Depiction of the characterization results revealed that FSCu possessed a considerable surface area (299.7 m 2 g −1 ) as well as pore volume (0.70 cm 3 g −1 ) than those of CuO/KCC-1 and CuO. Indeed, the excellent CuO dispersion and intense CuO-interaction resulted from the alternately aligned CuO and SiO2 in the fibrous framework. As a result of these great attributes, the FSCu photocatalyst recorded a superior yield of CH3 OH (412.4 µmol gcat −1 h −1 ) with triethylamine assistance as a sacrificial reductant, followed by CuO (310.3 µmol gcat −1 h −1 ) and CuO/KCC-1 (189.6 µmol gcat −1 h −1 ). Additionally, the ideal bandgap position for FSCu compared to CuO/KCC-1 contributed to the greater yield of CH3 OH. The parameter evaluations recorded that the highest yield of CH3 OH for FSCu was acquired at a catalyst of 0.6 g L −1, 100 mL min −1 of CO2, and the amount of TEA of about 50 mL. This paper also proposes a photoconversion mechanism for synthesized photocatalysts, as well as a comparative assessment of their performance with recently developed CuO-based photocatalysts.